Capital cities: Varieties and patterns of development and relocation. - Rossman, Vadim (Routledge, 2019)
Capital Cities studies the approaches and the methodologies that inform such decisions and debates. Special attention is given to the study of the universal patterns of relocation and patterns specific to particular continents and mega-regions and particular political regimes. The study emphasizes the role of capital city transfers in the context of nation- and state-building and offers a new framework for thinking about capital cities, identifying six strategies that drive these decisions, representing the economic, political, geographic, cultural and security considerations. Confronting the popular hyper-critical attitudes towards new designed capital cities, the author shows the complex motives that underlie the proposals and the important role that new capitals might play in conflict resolution in the context of ethnic, religious and regional rivalries and federalist transformations of the state, and is seeking to identify the success and failure factors and more efficient implementation strategies. Drawing upon the insights from spatial economics, comparative federalist studies, urban planning and architectural criticism, the book also traces the evolution of the concept of the capital city, showing that the design, iconography and the location of the capital city play a critical role in the success and the viability of the state.
Keywords: Hauptstadt; Umzug; Verlegung; Entscheidung; Stadtentwicklung; Internationaler Vergleich; Geschichte; Kolonialismus; Stadtsoziologie; Politikwissenschaft; Postkolonialismus